‘Holy worldliness’ in nineteenth-century England - Willmer, Haddon (Studies in church history, 1973)
If it had ever been coined, the slogan ‘holy worldliness’ would have been welcomed in nineteenth-century England. So many of the longings, and half-formed visions of the period seemed to be pressing in that direction. And yet the fact that it never appeared, so far as I know, suggests that the thinking of the time was somehow deeply inhibited. In this paper, I wish to try to show how close theologians and popular religious thinkers came to framing the concept of ‘holy worldliness’, and how and why they were held back.My reading has unfortunately been inadequate and this paper can be no more than a first impressionistic sketch. I have not taken the well trodden highroad of F. D. Maurice and Charles Kingsley and the like. This is not to deny their importance, but given a limited space, I want to explore some of the by-paths, if only to keep open the historian’s rights of way. Only as we walk them well shall we be able to understand die merits and demerits of the highroad. To speak plainly, figures like F. D. Maurice are studied too much in isolation from their context; even when this procedure does not lead to positive error, it cannot help but reduce claims for their special significance to mere assertions. To judge whether a man had a unique or seminal role involves comparing him with his competitors, and that means, doing equal justice to them all. By itself, the biographical method - the hero against a backcloth - gives no grounds for estimating the hero’s significance, since it has already been prejudged by the biographical form. But this reflection is no doubt an inaptly grandiose apology for the deficiencies of what I have to offer.